Boron-phosphorus co-doped high-adsorbability carbon-based solid acid catalyst as well as preparation method and application thereof

Through the preparation and application of a strongly adsorbed carbon-based solid acid catalyst co-doped boron and phosphorus, the disadvantages of acid catalysis during cellulose hydrolysis into sugar are solved, and efficient and environmentally friendly cellulose hydrolysis conversion is achieved, providing an efficient catalytic solution for biomass hydrolysis.

CN119702022APending Publication Date: 2025-03-28NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411984024.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art has disadvantages of acid catalysis in the process of cellulose hydrolysis into sugar, such as sugar acid separation, equipment corrosion, wastewater treatment and poor selectivity, and biological enzymes are fragile and difficult to recover, and reaction conditions are limited, making it difficult to meet the needs of short-cycle, low-cost, and large-scale catalytic.

Method used

By co-doping boron and phosphorus, a strong adsorption carbon-based solid acid catalyst is used to carry out hydrothermal carbonization reaction between the phosphorus source and the boron-containing carbon source or the carbon source boric acid mixture, a catalyst with rich -OH and stable -PO3H2 is prepared to achieve local strong adsorption and catalytic hydrolysis of cellulose.

Benefits of technology

In a mild reaction environment, the adsorption performance and catalytic efficiency of the catalyst are improved, and the efficient conversion of cellulose into high added value hydrolysate is achieved, which reduces the acid amount, and the catalyst can be recycled, making the synthesis route green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702022A_ABST
    Figure CN119702022A_ABST
Patent Text Reader

Abstract

The invention provides a boron-phosphorus co-doped high-adsorbability carbon-based solid acid catalyst as well as a preparation method and application thereof. The invention relates to a preparation method of a boron-phosphorus co-doped strong-adsorbability carbon-based solid acid catalyst, which comprises the following steps: (1) mixing a phosphorus source, a boron-containing carbon source or a carbon source and boric acid mixture according to a molar ratio of 1: 10-10: 1, then adding a solvent, and stirring or ultrasonically dispersing to obtain a mixed solution; and (2) carrying out hydrothermal carbonization reaction on the mixed solution at 120-280 DEG C for at least 3 hours, and after the reaction is finished, separating, washing and drying to obtain the boron-phosphorus co-doped strong-adsorbability carbon-based solid acid catalyst. According to the method disclosed by the invention, a large amount of-OH and-PO3H2 can be introduced in a relatively mild reaction environment, so that the prepared catalyst has richer-OH and stable-PO3H2, shows a local strong adsorption effect on cellulose, destroys a cellulose structure, and shows an excellent catalytic effect by combining a catalytic hydrolysis effect of-PO3H2 and double-group synergy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of hydrothermal carbon materials, and in particular to a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst and a preparation method and application thereof. Background Art

[0002] At present, the key bottleneck and important challenge for the success of the biorefining industry based on the glucose platform is to efficiently break the cellulose aggregation structure and β-1,4-glycosidic bonds by chemical methods. Usually, the saccharification of cellulose is carried out on homogeneous catalysts such as sulfuric acid and cellulase. However, the disadvantage of using homogeneous catalysts such as sulfuric acid and cellulase for cellulose saccharification is that acid catalysis has problems such as sugar-acid separation, equipment corrosion, wastewater treatment, and poor selectivity. Enzymes are fragile biological molecules, which are usually difficult to recover, and there is a narrow operating window for reaction temperature and solvent selection. Therefore, acids and biological enzymes as catalysts are difficult to meet the current urgent needs of short-term, low-cost, and large-scale catalytic hydrolysis of cellulose into sugars. Therefore, the use of more environmentally friendly and inexpensive chemical means to synthesize solid acids to catalyze cellulose into sugars has aroused great interest.

[0003] The highly efficient synergy between the adsorption domain and the catalytic domain in biological enzymes and the positive correlation between the strength of the adsorption and the catalytic efficiency are inspiring for the chemical synthesis of enzyme-mimicking solid acids. Therefore, catalysts containing adsorption groups such as -Cl, -OH and acidic groups such as -COOH and -SO3H have been developed one after another. However, these types of catalysts usually have the problem of insufficient number of functional groups and easy leaching of functional groups (-Cl, -SO3H, etc.), resulting in catalyst deactivation.

[0004] The researchers further discovered that the hydrothermal carbon surface has stable and abundant -OH, which can destroy the cellulose macrostructure by relying on the strong local adsorption between cellulose and cellulose. However, due to the lack of acidic groups, the catalyst cannot obtain a high glucose yield. Since then, studies have been reported one after another on the introduction of stable acidic groups such as -COOH and -PO3H2 on the surface of -OH-rich hydrothermal functional carbon to increase the glucose yield. However, there are few studies on the key factors affecting the efficiency of catalytic hydrolysis of cellulose into sugars, and the catalytic mechanism is still unclear; the cellulose hydrolysis efficiency is low. Therefore, in order to further improve the adsorption performance of the catalyst and improve the cellulose hydrolysis efficiency, B-OH and stable -PO3H2, which can provide stronger adsorption performance, seem to be a very promising combination. Summary of the invention

[0005] The present invention provides a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst and a preparation method and application thereof, so as to at least solve one of the technical problems existing in the prior art.

[0006] According to a first aspect of the present disclosure, a method for preparing a boron-phosphorus co-doped strongly adsorptive carbon-based solid acid catalyst is provided, comprising:

[0007] (1) mixing a phosphorus source, a boron-containing carbon source or a carbon source and a boric acid mixture at a molar ratio of 1:10 to 10:1, then adding a solvent, stirring or ultrasonically dispersing to obtain a mixed solution;

[0008] (2) subjecting the mixed solution to a hydrothermal carbonization reaction at 120-280° C. for at least 3 hours, and separating, washing, and drying after the reaction to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0009] In one embodiment, the molar ratio of the phosphorus source to the boron-containing carbon source is 5:1 to 1:5; the molar ratio of the phosphorus source to the carbon source boric acid mixture is 5:1 to 1:5;

[0010] In step (1), the concentration of the mixed solution is 0.1 to 10 mol / L.

[0011] In one embodiment, the phosphorus source is a mixture of one or more of phosphoric acid, phytic acid, phenylphosphoric acid, adenosine phosphate, phosphate and pyridoxal phosphate;

[0012] The boron-containing carbon source is an organic compound containing B-OH;

[0013] The carbon source boric acid mixture is a mixture of boric acid and a carbon source in a mass ratio of 1:5 to 15; wherein the carbon source is one or more of a sugar substance, a furan compound, and a benzene ring-containing compound;

[0014] The solvent is one of deionized water, an aqueous solvent and an organic solvent.

[0015] In one embodiment, the B-OH-containing organic compound is one or more of furanboric acid, phenylboric acid, 5-formaldehyde furan-2-boric acid, and 1,4-phenylenediboric acid;

[0016] The sugar substance is one or more of glucose, oligosaccharides, chitin, glucose derivatives, xylose and oligoxylose;

[0017] The furan compound is one or more of furfural, 5-hydroxymethylfurfural, furfuryl alcohol, and furoic acid;

[0018] The benzene ring-containing compound is one or more of p-toluenesulfonic acid, phenol, phloroglucinol, and benzyl alcohol;

[0019] The aqueous phase solvent is one of a sodium hydroxide aqueous solution, an alkaline urea aqueous solution, a NaOH / thiourea aqueous solution, a quaternary ammonium salt aqueous solution, a quaternary phosphonium salt aqueous solution, and a molten inorganic salt hydrate;

[0020] The organic solvent is a mixed solvent of lithium chloride and N,N-dimethylacetamide, an ionic liquid, or a low eutectic solvent.

[0021] In one embodiment, in step (1), the stirring time is 0.1 to 2 hours;

[0022] The ultrasonic dispersion time is 5 to 60 minutes;

[0023] In step (2), the temperature of the hydrothermal carbonization reaction is 150-250°C.

[0024] According to a second aspect of the present disclosure, a boron-phosphorus co-doped strongly adsorptive carbon-based solid acid catalyst is provided, which is prepared by the preparation method described above.

[0025] According to a third aspect of the present disclosure, there is provided an application of a boron-phosphorus co-doped strongly adsorptive carbon-based solid acid catalyst in biomass hydrolysis conversion.

[0026] In one embodiment, the biomass raw material is one or more of cellulose, chitosan, microcrystalline cellulose, hemicellulose, and native lignocellulose;

[0027] The biomass is hydrolyzed and converted into one of soluble oligosaccharides, cellobiose, glucose, furfural, HMF, levulinic acid, formic acid, ethylene glycol, 1,3-propylene glycol, fructose, γ-valerolactone, methanol, xylose, dietary fiber, xylo-oligosaccharides, arabinose and rhamnose.

[0028] In one embodiment, the catalyst and the biomass raw material are mixed in a solvent system and hydrolyzed and converted, wherein the mass ratio of the catalyst to the biomass raw material is 1:0.1 to 0.1:1, the reaction temperature is 120 to 250°C, the reaction time is 1 to 72 hours, and the solvent system is one of pure water, a dilute acid solution, and an alcohol solution; the dilute acid solution is a mixture of one or more of maleic acid, oxalic acid, acetic acid, p-toluenesulfonic acid and formic acid; the alcohol solution is methanol or ethanol.

[0029] In one embodiment, the catalyst and the biomass raw material are mixed in a solvent system and hydrolyzed and converted using microwave drive, wherein the mass ratio of the catalyst to the biomass raw material is 1:0.1 to 0.1:1, the reaction temperature is 120 to 250°C, the time is 1 to 120 min, the power of the microwave drive is 10 to 800 W, and the solvent system is one of pure water, a dilute acid solution, and an alcohol solution; the dilute acid solution is a mixture of one or more of maleic acid, oxalic acid, acetic acid, p-toluenesulfonic acid and formic acid; the alcohol solution is methanol or ethanol.

[0030] Compared with the prior art, the advantages of the present application are: 1) In the method of the present application, a large amount of -OH and -PO3H2 can be introduced in a milder reaction environment, so that the prepared catalyst has richer -OH and stable -PO3H2, showing a strong local adsorption effect on cellulose, destroying the cellulose structure, and combined with the catalytic hydrolysis effect of -PO3H2, the two groups synergistically show an excellent catalytic effect.

[0031] 2) The synthetic route of the boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst prepared in the present application is green and environmentally friendly, simple to operate, has low equipment cost, has high content of surface grafted phosphoric acid groups and hydroxyl groups, good hydrophilicity, and can be recycled.

[0032] 3) The catalyst prepared by the method of the present application adopts a very safe hydrolysis system in the process of biomass hydrolysis and conversion into sugar, using pure water or dilute acid or alcohol solution, which can effectively reduce the amount of acid in the system to 1 / 4 of the existing method; the catalyst can realize the catalytic conversion of biomass hydrothermal decomposition into hydrolysis products with high added value under mild conditions.

[0033] 4) The catalyst prepared by the method of the present application has a high biomass conversion rate during biomass hydrolysis conversion.

[0034] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0036] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0037] Figure 1 The following is a schematic diagram showing a method for preparing a catalyst according to an embodiment of the present disclosure and a process flow diagram of the catalyst used for biomass hydrolysis and conversion (taking cellulose as an example);

[0038] Figure 2 shows a SEM image of the catalyst of Example 1 of the present disclosure;

[0039] Figure 3 shows a particle size distribution diagram of the catalyst of Example 1 of the present disclosure;

[0040] Figure 4 shows an EDS graph of the catalyst of Example 1 of the present disclosure;

[0041] Figure 5 shows an infrared spectrum of the catalyst of Example 1 of the present disclosure;

[0042] Figure 6 The SEM image of the interaction between the solid acid catalyst and cellulose in the process of biomass hydrolysis conversion using the catalyst of Example 1 of the present disclosure is shown;

[0043] Figure 7 The graphs of temperature and hydrolysis product yield and cycle performance of the catalyst of Example 10 of the present disclosure used in the biomass hydrolysis conversion process are shown. DETAILED DESCRIPTION

[0044] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0045] According to one embodiment of the present disclosure, the present invention provides a method for preparing a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst. The preparation method comprises:

[0046] Step (1), mixing a phosphorus source, a boron-containing carbon source or a carbon source and a boric acid mixture at a molar ratio of 1:10 to 10:1, then adding a solvent, stirring or ultrasonically dispersing to obtain a mixed solution;

[0047] Step (2), subjecting the mixed solution to a hydrothermal carbonization reaction at 120-280° C. for at least 3 hours, separating and washing the filtrate until the filtrate is colorless and transparent, and drying to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst after the reaction is completed.

[0048] The method of the present application is simple in process, and only needs to use a phosphorus source, a boron-containing carbon source or a carbon source boric acid mixture, and then perform hydrothermal carbonization to synthesize in situ a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst (referred to as "catalyst", "solid acid catalyst", the same below). The catalyst is used for more abundant -OH and stable -PO3H2, and exhibits a local strong adsorption effect on woody biomass (referred to as "biomass") to destroy the biomass structure. Combined with the catalytic hydrolysis of -PO3H2, the double groups synergistically exhibit an excellent catalytic effect, thereby improving the conversion rate of biomass.

[0049] The preparation process of the solid acid catalyst of the present application is as follows Figure 1As shown, the solid acid catalyst has a strong local adsorption capacity and can be adsorbed and anchored on the surface of woody biomass (including cellulose, chitosan, microcrystalline cellulose, hemicellulose, native woody cellulose raw materials and the above raw materials after pretreatment), effectively destroying the surface structure of woody biomass to fragment it during the detachment process, and providing a local stable microenvironment for the hydrolysis of woody biomass by -PO3H2. B-OH and -PO3H2 work together to efficiently catalyze the decomposition of woody biomass, realize the high-value application of non-food woody biomass, and provide a rich woody biomass carbon source for woody biomass energy and materialization.

[0050] The principle of the catalyst preparation and use for biomass hydrolysis conversion in this application is: Figure 1 As shown, first, the particles of phosphorus source, boron-containing carbon source or carbon source boric acid mixture complete primary particle formation and polymerization in the solvent to form a carbon skeleton, and the functional groups are enriched on the surface of the carbon skeleton to obtain a catalyst. When the catalyst is used for biomass hydrolysis and conversion, for example, for cellulose hydrolysis, the catalyst in the solvent gradually approaches the cellulose surface, and a strong local adsorption is formed between the catalyst and the cellulose, so that the catalyst gradually interacts with the cellulose, and the microscopic structure of the cellulose surface is destroyed. In this process, the solid acid first approaches the cellulose, and the abundant -OH on the surface of the solid acid forms a hydrogen bond with the -OH on the surface of the cellulose, anchoring the solid acid on the surface of the cellulose, forming a stable local hydrolysis microenvironment for the hydrolysis of the β-1,4-glycosidic bond by the acidic groups on the surface of the solid acid, and releasing glucose. Enzyme-like efficient hydrolysis of cellulose is achieved.

[0051] Among them, preferably, the molar ratio of the phosphorus source and the boron-containing carbon source is 5:1 to 1:5; the molar ratio of the phosphorus source and the carbon source boric acid mixture is 5:1 to 1:5; for example, the molar ratio of the phosphorus source, the boron-containing carbon source or the carbon source boric acid mixture is 1:10, 1:5, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1.

[0052] Preferably, in step (1), the concentration of the mixed solution is 0.1 to 10 mol / L.

[0053] For example, in step (1), the phosphorus source is a mixture of one or more of phosphoric acid, phytic acid, phenylphosphoric acid, adenosine phosphate, phosphate and pyridoxal phosphate; all of which can be used to modify the phosphoric acid group on the catalyst surface in the method of the present application.

[0054] In step (1), the boron-containing carbon source is an organic compound containing B-OH;

[0055] In step (1), the carbon source boric acid mixture is a mixture of boric acid and a carbon source in a mass ratio of 1:5 to 15; wherein the carbon source is one or more of a carbohydrate, a furan compound, and a benzene ring-containing compound;

[0056] In step (1), the solvent is one of deionized water, an aqueous solvent, and an organic solvent.

[0057] More preferably, for example, the organic compound containing B-OH is one or more of furanboric acid, phenylboric acid, 5-formaldehyde furan-2-boric acid, and 1,4-phenylenediboric acid;

[0058] The carbohydrate substance is one or more of glucose, oligosaccharides, chitin, glucose derivatives, xylose and oligosaccharides;

[0059] The furan compound is one or more of furfural, 5-hydroxymethylfurfural, furfuryl alcohol, and furoic acid;

[0060] The benzene ring-containing compound is one or more of p-toluenesulfonic acid, phenol, phloroglucinol, and benzyl alcohol;

[0061] The aqueous phase solvent is one of a sodium hydroxide aqueous solution, an alkaline urea aqueous solution, a NaOH / thiourea aqueous solution, a quaternary ammonium salt aqueous solution, a quaternary phosphonium salt aqueous solution, and a molten inorganic salt hydrate;

[0062] The organic solvent is a mixed solvent of lithium chloride and N,N-dimethylacetamide, an ionic liquid, or a low eutectic solvent.

[0063] For example, in step (1), the stirring time is 0.1 to 2 h; the ultrasonic dispersion time is 5 to 60 min, and preferably, the ultrasonic dispersion time is 5 to 30 min.

[0064] For example, in step (2), the temperature of the hydrothermal carbonization reaction is 150-250°C.

[0065] For example, in step (2), the mixed solution is subjected to hydrothermal carbonization reaction in a closed container. For example, the closed container is a high-pressure reactor with a polytetrafluoroethylene liner.

[0066] For example, in step (2), washing is performed with one of deionized water, anhydrous ethanol, methanol and acetone, and then drying is performed in an oven, and the drying temperature is preferably 80° C. and the drying time is 24 hours.

[0067] According to one embodiment of the present disclosure, the present invention also provides a boron-phosphorus co-doped strongly adsorptive carbon-based solid acid catalyst, which is prepared by the above-mentioned preparation method.

[0068] According to one embodiment of the present disclosure, the present invention also provides an application of a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in biomass hydrolysis conversion. For example, the catalyst prepared by the method of the present application can be mixed with a biomass raw material in a solvent system to hydrolyze the biomass raw material into a hydrolyzate with high added value. The hydrolyzate includes, but is not limited to: soluble oligosaccharides (such as soluble oligoglucose), cellobiose, glucose, furfural, HMF (5-hydroxymethylfurfural), levulinic acid, formic acid, ethylene glycol, 1,3-propylene glycol, fructose, γ-valerolactone, methanol, xylose, dietary fiber, oligoxylose, arabinose, and rhamnose.

[0069] For example, the biomass raw material is one or more of cellulose, chitosan, microcrystalline cellulose, hemicellulose, and primary lignocellulose raw materials. Further, one or more of cellulose, chitosan, microcrystalline cellulose, hemicellulose, and primary lignocellulose raw materials are first pretreated, and then used as biomass raw materials for subsequent hydrolysis conversion. Before the hydrolysis conversion, the biomass raw materials are first pretreated in order to improve the hydrolysis efficiency. Specific pretreatment methods include physical methods (such as mechanical pretreatment, microwave pretreatment, ultrasonic pretreatment), chemical methods (such as acid pretreatment, alkali pretreatment, organic solvent pretreatment, ionic liquid pretreatment, and low eutectic solvent pretreatment), physicochemical methods (such as steam explosion pretreatment and hydrothermal pretreatment, etc.), and microbial methods, etc.

[0070] Furthermore, the crystallinity of celluloses such as microcrystalline cellulose, regenerated cellulose, corncob cellulose, viscose cellulose, cotton cellulose, and cuprammonium cellulose is between 5 and 75%, and the degree of polymerization is between 30 and 7500.

[0071] Preferably, the catalyst and the biomass raw material are mixed in a solvent system and hydrolyzed and converted, wherein the mass ratio of the catalyst to the biomass raw material is 1:0.1 to 0.1:1, the reaction temperature is 120 to 250°C, the reaction time is 1 to 72 hours, and the solvent system is one of pure water, a dilute acid solution, and an alcohol solution; the dilute acid solution is a mixture of one or more of maleic acid, oxalic acid, acetic acid, p-toluenesulfonic acid, and formic acid; the alcohol solution is methanol or ethanol.

[0072] Preferably, the catalyst and the biomass raw material are mixed in a solvent system and hydrolyzed and converted using microwave drive, wherein the mass ratio of the catalyst to the biomass raw material is 1:0.1 to 0.1:1, the reaction temperature is 120 to 250°C, the time is 1 to 120 min, the power of the microwave drive is 10 to 800 W, and the solvent system is one of pure water, a dilute acid solution, and an alcohol solution; the dilute acid solution is a mixture of one or more of maleic acid, oxalic acid, acetic acid, p-toluenesulfonic acid and formic acid; the alcohol solution is methanol or ethanol.

[0073] The present application overcomes the problems of weak adsorption of existing solid acids and deactivation of catalysts caused by leaching of functional groups, and provides a method for preparing a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst. The boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst prepared by this method has more abundant -OH and stable -PO3H2, and exhibits a local strong adsorption effect on biomass, such as cellulose, destroying the cellulose structure. Combined with the catalytic hydrolysis effect of -PO3H2, the two groups synergistically exhibit excellent catalytic effects.

[0074] The preparation method of the boron-phosphorus co-doped strongly adsorbable carbon-based solid acid catalyst of the present application can introduce a large amount of -OH and -PO3H2 in a relatively mild reaction environment. The synthesis mechanism is to introduce a phosphoric acid group on the furan ring of the carbon source compound through an in-situ condensation reaction under a hydrothermal system to form an intermediate, and then hydrothermally carbonize and polymerize into carbon-based microspheres. The hydrothermal carbon-based microspheres co-doped with -OH and -PO3H2 are defined as solid acid catalysts with a high amount of -PO3H2 and -OH.

[0075] This application aims at the shortcomings of existing carbon-based catalysts in biomass hydrolysis catalytic reactions, including the limited number of catalytic groups of solid acid catalysts, insufficient stability, poor catalytic activity, poor selectivity, and the fact that the hydrolysis system is mostly toxic solvents. A method using pure water or dilute acid solution or alcohol solution as the hydrolysis system is proposed, which can effectively reduce the amount of acid in the system to 1 / 4 of the existing method. The prepared carbon-based solid acid catalyst can realize the catalytic conversion of biomass hydrothermal depolymerization into high value-added hydrolysis products under mild conditions.

[0076] In summary, the synthesis route of the boron and phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst prepared in this scheme is green and environmentally friendly, simple to operate, has low equipment cost, has high content of surface grafted phosphate groups and hydroxyl groups, good hydrophilicity, can be recycled, and has high biomass hydrolysis conversion efficiency.

[0077] The present application is further described in detail below with reference to the accompanying drawings:

[0078] Example 1

[0079] A method for preparing a boron-phosphorus co-doped carbon-based solid acid catalyst with strong adsorption, comprising the steps of:

[0080] Step (1), according to the molar ratio of boron-containing carbon source to phosphorus source being 1:1, 5-formaldehyde furan-2-boric acid as boron-containing carbon source and concentrated phosphoric acid (concentration of 85%) as phosphorus source are accurately weighed respectively; deionized water is then added, and ultrasonic dispersion is performed for 20 minutes to obtain a mixed solution; wherein the concentration of the mixed solution is 5M.

[0081] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 180° C., and the reaction time to 10 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80° C. for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0082] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0083] Step (1) 0.2g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst is mixed with 0.2g of corn cob cellulose (crystallinity of 35% and polymerization degree of 530), and added to 20mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 180°C for 3h. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried for the next reaction, and the filtrate is used for product analysis. The corn cob cellulose conversion rate is 100wt%, and the glucose yield is 85wt%. Among them, the cellulose conversion rate refers to the ratio of the mass of the converted cellulose to the mass of the added cellulose. The glucose yield refers to the mass ratio of glucose in the solution to the added cellulose; for example, in this embodiment 1, 85% of the cellulose is converted into glucose.

[0084] Step (2), according to step (1), the catalyst is recycled for 10 times, the cellulose conversion rate is still above 95wt%, and the glucose yield is above 80wt%.

[0085] Example 2

[0086] A method for preparing a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst comprises the following steps:

[0087] Step (1): according to the molar ratio of boron-containing carbon source to phosphorus source being 1:10; accurately weighing 5-formaldehyde furan-2-boric acid as boron-containing carbon source and phytic acid as phosphorus source; then adding deionized water, ultrasonically dispersing for 30 minutes, to obtain a mixed solution; wherein the concentration of the mixed solution is 5M.

[0088] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 200° C., and the reaction time to 10 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80° C. for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0089] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0090] Step (1), 0.1g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst and 1g of microcrystalline cellulose (crystallinity of 70%, degree of polymerization of 105) are mixed and added to 50mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 200°C for 4h. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried and used for the next reaction, and the filtrate is used for product analysis. The conversion rate of microcrystalline cellulose is 95wt%, and the glucose yield is 72wt%.

[0091] Step (2), according to step (1), the catalyst is recycled for 10 times, the conversion rate of microcrystalline cellulose is still above 89wt%, and the glucose yield is above 65wt%.

[0092] Example 3

[0093] A method for preparing a boron-phosphorus co-doped carbon-based solid acid catalyst with strong adsorption, comprising the steps of:

[0094] Step (1): mixing a carbon source boric acid mixture and a phosphorus source in a molar ratio of 1:1; wherein the carbon source boric acid mixture includes glucose and boric acid in a mass ratio of 5:1, and pyridoxal phosphate is used as the phosphorus source; then adding deionized water, ultrasonically dispersing for 10 minutes, to obtain a mixed solution; wherein the concentration of the mixed solution is 1M.

[0095] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 200°C and the reaction time to 4 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80°C for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0096] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0097] Step (1) 0.2g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst and 1g of chitosan (crystallinity of 26%, degree of polymerization of 180) are mixed and added to 20mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 160°C for 2.5h. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried and used for the next reaction, and the filtrate is used for product analysis. The chitosan conversion rate is 97wt%, and the glucose yield is 64wt%.

[0098] Step (2), according to step (1), the catalyst is recycled for 15 times, the chitosan conversion rate is still above 90wt%, and the glucose yield is above 60wt%.

[0099] Example 4

[0100] A method for preparing a boron and phosphorus co-doped carbon-based solid acid catalyst with strong adsorption, comprising the steps of:

[0101] Step (1): mixing a carbon source boric acid mixture and a phosphorus source in a molar ratio of 1:5; wherein the carbon source boric acid mixture includes 5-hydroxymethylfurfural and boric acid in a mass ratio of 10:1, and phytic acid is used as a phosphorus source; then adding deionized water, ultrasonically dispersing for 60 minutes, to obtain a mixed solution; wherein the concentration of the mixed solution is 3M.

[0102] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 180° C., and the reaction time to 16 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80° C. for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0103] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0104] Step (1) 0.5 g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst and 0.5 g of microcrystalline cellulose (crystallinity of 68%, degree of polymerization of 300) are mixed and added to 60 mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 200° C. for 2 hours. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried and used for the next reaction, and the filtrate is used for product analysis. The conversion rate of microcrystalline cellulose is 85 wt%, and the glucose yield is 59 wt%.

[0105] Step (2), according to step (1), the catalyst is recycled for 30 times, the conversion rate of microcrystalline cellulose is still above 80wt%, and the glucose yield is above 52wt%.

[0106] Example 5

[0107] A method for preparing a boron-phosphorus co-doped carbon-based solid acid catalyst with strong adsorption, comprising the steps of:

[0108] Step (1): according to the molar ratio of boron-containing carbon source to phosphorus source being 5:1; accurately weighing furanboric acid as carbon source and phytic acid as phosphorus source respectively; then adding deionized water, ultrasonically dispersing for 10 minutes, to obtain a mixed solution; wherein the concentration of the mixed solution is 0.5M.

[0109] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 160° C., and the reaction time to 24 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80° C. for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0110] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0111] Step (1) 1g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst is mixed with 0.5g of microcrystalline cellulose (crystallinity of 55%, degree of polymerization of 125), and added to 10mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 220°C for 1h. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried and used for the next reaction, and the filtrate is used for product analysis. The microcrystalline cellulose conversion rate is 100wt%, and the glucose yield is 53wt%.

[0112] Step (2), according to step (1), the catalyst is recycled for 10 times, the cellulose conversion rate is still above 95wt%, and the glucose yield is above 50wt%.

[0113] Example 6

[0114] A method for preparing a boron-phosphorus co-doped carbon-based solid acid catalyst with strong adsorption, comprising the steps of:

[0115] Step (1): according to the molar ratio of boron-containing carbon source to phosphorus source being 10:1; accurately weighing phenylboric acid as carbon source and phytic acid as phosphorus source respectively; then adding deionized water, ultrasonically dispersing for 30 minutes, to obtain a mixed solution; wherein the concentration of the mixed solution is 2M.

[0116] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 220° C., and the reaction time to 4 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80° C. for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0117] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0118] Step (1) 1g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst and 0.5g of microcrystalline cellulose (crystallinity of 60%, degree of polymerization of 95) are mixed and added to 30mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 220°C for 1.5h. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried for the next reaction, and the filtrate is used for product analysis. The cellulose conversion rate is 100wt%, and the glucose yield is 80wt%.

[0119] Step (2), according to step (1), the catalyst is recycled for 25 times, the cellulose conversion rate is still above 98wt%, and the glucose yield is above 76wt%.

[0120] Example 7

[0121] A method for preparing a boron-phosphorus co-doped carbon-based solid acid catalyst with strong adsorption, comprising the steps of:

[0122] Step (1): according to the molar ratio of boron-containing carbon source to phosphorus source being 1:10; accurately weighing 4-hydroxyphenylboric acid as carbon source and phytic acid as phosphorus source respectively; then adding deionized water, ultrasonically dispersing for 30 minutes, to obtain a mixed solution; wherein the concentration of the mixed solution is 5M.

[0123] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 190° C., and the reaction time to 18 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80° C. for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0124] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0125] Step (1) 1g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst is mixed with 0.1g of microcrystalline cellulose (crystallinity of 72%, degree of polymerization of 350), and added to 40mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 150°C for 6h. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried for the next reaction, and the filtrate is used for product analysis. The cellulose conversion rate is 100wt%, and the glucose yield is 83wt%.

[0126] Step (2), according to step (1), the catalyst is recycled for 30 times, the cellulose conversion rate is still above 96wt%, and the glucose yield is above 80wt%.

[0127] Example 8

[0128] A method for preparing a boron-phosphorus co-doped carbon-based solid acid catalyst with strong adsorption, comprising the steps of:

[0129] Step (1): according to the molar ratio of boron-containing carbon source to phosphorus source being 3:1; accurately weighing 1,4-phenyldiboric acid as a carbon source and phytic acid as a phosphorus source; then adding deionized water, ultrasonically dispersing for 30 minutes, to obtain a mixed solution; wherein the concentration of the mixed solution is 2.5M.

[0130] Step (2), placing the mixed solution in a high-pressure reactor, sealing the high-pressure reactor and transferring it to an explosion-proof homogeneous reaction box, adjusting the reaction temperature to 180° C., and the reaction time to 24 hours; after the reaction is completed, cooling to room temperature, performing solid-liquid separation by suction filtration, and thoroughly washing the retained solid with anhydrous ethanol and water, transferring the solid to an oven, and drying at 80° C. for 12 hours to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

[0131] The application of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst in the hydrolysis of biomass into glucose comprises the following steps:

[0132] Step (1) 0.3g of boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst and 0.6g of regenerated cellulose (crystallinity of 15%, degree of polymerization of 86) are mixed and added to 20mL of deionized water to obtain a mixed solution; the mixed solution is added to a high-pressure reactor, and hydrothermally reacted at 170°C for 3h. After the reaction is completed, a hydrolyzate is prepared, filtered, and the residue is dried for the next reaction, and the filtrate is used for product analysis. The cellulose conversion rate is 100wt%, and the glucose yield is 78wt%.

[0133] Step (2), according to step (1), the catalyst is recycled for 30 times, the cellulose conversion rate is still above 98wt%, and the glucose yield is above 75wt%.

[0134] Example 9

[0135] This embodiment 9 is substantially the same as embodiment 1, except that in the preparation method of the solid acid catalyst of this embodiment 9, the reaction temperature of step 2) is 150°C.

[0136] The solid acid catalyst obtained in Example 9 was used to hydrolyze corncob cellulose and convert it into glucose, and the specific steps were as in Example 1. The conversion rate of corncob cellulose was 92 wt %, and the glucose yield was 54 wt %.

[0137] Example 10

[0138] This embodiment 10 is substantially the same as embodiment 1.

[0139] The solid acid catalyst obtained in Example 10 was used to hydrolyze corncob cellulose and convert it into glucose. The specific steps were referred to Example 1, but the hydrothermal reaction conditions in Example 10 were 170° C. for 3 h. The conversion rate of corncob cellulose was 100 wt%, and the glucose yield was 71.24 wt%.

[0140] Comparative Example 1

[0141] Comparative Example 1 is substantially the same as Example 1, except that in the preparation method of the solid acid catalyst of Comparative Example 1, the reaction temperature of step 2) is 100°C.

[0142] The solid acid catalyst obtained in Comparative Example 1 was used to hydrolyze corncob cellulose and convert it into glucose, and the specific steps were as in Example 1. The conversion rate of corncob cellulose was 20.56 wt %, and the glucose yield was 3.82 wt %.

[0143] Characterization and testing

[0144] 1) The catalyst prepared in Example 1 was subjected to scanning electron microscopy, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the solid acid catalyst has good sphericity and uniformity.

[0145] 2) The particle size distribution of the catalyst prepared in Example 1 is as follows Figure 3 shown.

[0146] The particle size of the catalyst prepared by the method of the present application is in the range of 10 nm to 15 μm. Figure 3 It can be concluded that the average particle size of the catalyst in Example 1 is 3.36 μm. Figure 3 It can also be concluded that the catalyst of the present application is a boron-phosphorus co-doped carbon-based microsphere with a particle size of 1 to 7 μm, and the catalyst particle size distribution is mainly concentrated in the range of 2 to 5 μm.

[0147] 3) The catalyst prepared in Example 1 was subjected to EDS test, and the results were as follows: Figure 4 As shown. Figure 4 It can be seen that C, P, B, and O elements are evenly distributed in the catalyst.

[0148] In addition, the DNS method was used to detect the -OH and acidic group content on the surface of the solid acid. Due to the presence of B-OH, the surface -OH content is 1 to 50 mmol / g, which is much higher than the -OH content on the surface of traditional hydrothermal carbon. The local strong adsorption between the huge amount of -OH and the biomass is significantly stronger than that of the -Cl group. The content of -PO3H2 is 0.1 to 10 mmol / g, and its stability is significantly higher than that of -SO3H, which is conducive to the reuse of the solid acid.

[0149] 4) The solid acid catalyst prepared in Example 1 was tested by infrared spectroscopy. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that 750-663cm -1 The CP bond is at 1166cm -1 PO / CO, 1035cm -1 and 900cm -1 The characteristic peak of P=O is at 1027cm -1 The characteristic peak of B-OH is shown in Figure 1, indicating that the catalyst contains a large amount of B-OH. This shows that the catalyst of Example 1 was successfully prepared.

[0150] 5) The scanning electron microscopy image of the solid acid catalyst used in the biomass hydrolysis conversion process in Example 1 is as follows: Figure 6 As shown, from Figure 6 It can be seen that in an aqueous environment, a strong adsorption effect is formed between the -OH on the surface of the solid acid catalyst and cellulose, and the catalyst is anchored on the surface of cellulose, providing a stable local environment for the phosphate groups on the catalyst surface to hydrolyze cellulose.

[0151] 6) This application further explores the effects of reaction temperature and time on the conversion rate of biomass raw materials, the yield of hydrolyzed products, and the relationship between the number of catalyst cycles and the yield of hydrolyzed products during biomass hydrolysis. Taking Example 10 as an example, the conversion rate of biomass raw materials, the yield of hydrolyzed products, and the number of catalyst cycles when the catalyst is applied to biomass hydrolysis conversion at a temperature of 150 to 170°C are analyzed. The results are as follows: Figure 7 As shown. Figure 7 As can be seen. Figure 7 As shown in a, with the increase of temperature and time, the cellulose conversion rate (Cellulose conversion) showed an upward trend, and the highest conversion rate was 100%. However, the total reducing sugar (Reducing sugar) and glucose (Glucose) yields showed a trend of first increasing and then decreasing with the increase of temperature and time, and the highest glucose yield was 70.24wt%. This is because the increase of temperature and the extension of time are conducive to the conversion of cellulose to glucose, but too high temperature and too long time will promote side reactions, causing glucose to further degrade into other small molecular byproducts. Figure 7 As shown in b, the catalyst also has excellent recycling performance. After 20 cycles, the cellulose conversion rate still reaches 99wt% and the glucose yield is 64wt%.

[0152] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.

[0153] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0154] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst, characterized in that: include: (1) mixing a phosphorus source, a boron-containing carbon source or a carbon source and a boric acid mixture at a molar ratio of 1:10 to 10:1, then adding a solvent, stirring or ultrasonically dispersing to obtain a mixed solution; (2) subjecting the mixed solution to a hydrothermal carbonization reaction at 120-280° C. for at least 3 hours, and separating, washing, and drying after the reaction to obtain a boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the phosphorus source to the boron-containing carbon source is 5:1 to 1:5; The molar ratio of the phosphorus source and the carbon source boric acid mixture is 5:1 to 1:5; In step (1), the concentration of the mixed solution is 0.1 to 10 mol / L.

3. The preparation method according to claim 1, characterized in that: The phosphorus source is a mixture of one or more of phosphoric acid, phytic acid, phenylphosphoric acid, adenosine phosphate, phosphate and pyridoxal phosphate; The boron-containing carbon source is an organic compound containing B-OH; The carbon source boric acid mixture is a mixture of boric acid and a carbon source in a mass ratio of 1:5 to 15; wherein the carbon source is one or more of a sugar substance, a furan compound, and a benzene ring-containing compound; The solvent is one of deionized water, an aqueous solvent and an organic solvent.

4. The preparation method according to claim 3, characterized in that: The B-OH-containing organic compound is one or more of furanboric acid, phenylboric acid, 5-formaldehyde furan-2-boric acid, and 1,4-phenylenediboric acid; The sugar substance is one or more of glucose, oligosaccharides, chitin, glucose derivatives, xylose and oligoxylose; The furan compound is one or more of furfural, 5-hydroxymethylfurfural, furfuryl alcohol, and furoic acid; The benzene ring-containing compound is one or more of p-toluenesulfonic acid, phenol, phloroglucinol, and benzyl alcohol; The aqueous phase solvent is one of a sodium hydroxide aqueous solution, an alkaline urea aqueous solution, a NaOH / thiourea aqueous solution, a quaternary ammonium salt aqueous solution, a quaternary phosphonium salt aqueous solution, and a molten inorganic salt hydrate; The organic solvent is a mixed solvent of lithium chloride and N,N-dimethylacetamide, an ionic liquid, or a low eutectic solvent.

5. The preparation method according to claim 1, characterized in that: In step (1), the stirring time is 0.1 to 2 h; The ultrasonic dispersion time is 5 to 60 minutes; In step (2), the temperature of the hydrothermal carbonization reaction is 150-250°C.

6. A boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 5.

7. Use of the boron-phosphorus co-doped strongly adsorbent carbon-based solid acid catalyst according to claim 6 in biomass hydrolysis conversion.

8. The use according to claim 7, characterized in that: The biomass raw material is one or more of cellulose, chitosan, microcrystalline cellulose, hemicellulose, and native lignocellulose; The biomass is hydrolyzed and converted into one of soluble oligosaccharides, cellobiose, glucose, furfural, HMF, levulinic acid, formic acid, ethylene glycol, 1,3-propylene glycol, fructose, γ-valerolactone, methanol, xylose, dietary fiber, xylo-oligosaccharides, arabinose and rhamnose.

9. The use according to claim 7, characterized in that: The catalyst and the biomass raw material are mixed in a solvent system and hydrolyzed and converted, wherein the mass ratio of the catalyst to the biomass raw material is 1:0.1-0.1:1, the reaction temperature is 120-250°C, the reaction time is 1-72h, and the solvent system is one of pure water, dilute acid solution, and alcohol solution; the dilute acid solution is a mixture of one or more of maleic acid, oxalic acid, acetic acid, p-toluenesulfonic acid and formic acid; the alcohol solution is methanol or ethanol.

10. The use according to claim 7, characterized in that: The catalyst and the biomass raw material are mixed in a solvent system and hydrolyzed and converted by microwave driving, wherein the mass ratio of the catalyst to the biomass raw material is 1:0.1-0.1:1, the reaction temperature is 120-250°C, the reaction time is 1-120 min, the microwave driving power is 10-800 W, the solvent system is one of pure water, dilute acid solution, and alcohol solution; the dilute acid solution is a mixture of one or more of maleic acid, oxalic acid, acetic acid, p-toluenesulfonic acid and formic acid; the alcohol solution is methanol or ethanol.

Citation Information

Patent Citations

  • Boron-phosphorus co-doped metal-free carbon-based catalytic material as well as preparation method and application thereof

    CN114570351A

  • Boron-doped carbon-based catalytic accelerator as well as preparation method and application thereof

    CN115301221A

  • Phosphoric acid group modified hydroxyl-rich carbon material and application thereof

    CN116239104A

  • Difunctional carbon-based catalyst and application thereof

    CN117960153A